HUBUNGAN KEAKTIFAN DALAM KELAS IBU HAMIL TERHADAP PENGETAHUAN TENTANG KB PASCA PERSALINAN DI RUMAH SAKIT WAVA HUSADA KEPANJEN: THE CORRELATION BETWEEN ACTIVENESS PREGNANT WOMEN CLASSES AND THE KNOWLEDGE OF POSTPARTUM KB AT WAVA HUSADA HOSPITAL - Ratna, Tantri Yunita; Sa’adah, Sri Wahyuning (LPPM STIKes Bahrul Ulum Jombang, 2024)
Background : The results of a preliminary study conducted on 10 pregnant women, there were only 3 people who could answer about postpartum contraception planning, so researchers were interested in knowing more about the relationship between the activeness of the pregnant women class to knowledge about postpartum contraception planning. Subjects and Methods : This research uses Correlational Analytic Design and Cross Sectional Time Approach. The total population is 157 pregnant women and the samples used are 62 samples. The research instrument used was a questionnaire. Results : Of this study indicate that the majority of respondents who attended classes for pregnant women were active in attending classes for pregnant women as many as 37 people, the knowledge of pregnant women about family planning after childbirth was dominant in respondents having good knowledge with a value of ≥ 60%, namely 53 people. The results of the Chi Square test showed that there was a relationship between the active participation of pregnant women in classes and the knowledge of pregnant women about postpartum contraception planning as evidenced by a P value of 0.000 <0.05. Conclusion : Most pregnant woman active and understand well about the knowledge of postpartum KB in pregnancy class.